Hubungan Tingkat Kepedulian Orang Tua terhadap Status Oral Hygiene Anak Berkebutuhan Khusus - Citra Lestari; Valendriyani Ningrum; Ika Andriani; Dwi Windu (Universitas Sam Ratulangi, 2023)
Abstract: Oral health problems among special needs children (SNC) is a priority and concern of all parties, both parents/caregivers, dentists and health policy makers both nationally and regionally as soon as possible. This study aimed to determine the relationship between the level of parental care and the oral hygiene of children at SLB Wacana Asih, Padang. This was an analytical and survey study with a cross-sectional design. Sampling was performed by using total sampling, consisting of parents of SNC and the SNC as many as 82 children. Data were analyzed using the Spearman Rank test with a significance level of p<0.05. The results showed that parent’s attention to the dental and oral hygiene of SNC was 53.66% in the good category and 46.445% in the moderate category. Furthermore, the results of the examination of the oral hygiene status of SNC showed various levels of status, as follows: good (45.1%), moderate (28%), and poor (26.8%). The statistical correlation test obtained a p-value of 0.000 which indicated that there was a significant relationship between parental care and the oral hygiene status of SNC with a correlation coefficient of r 0.699, which means a strong positive relationship. In conclusion, the higher the concern of parents, the better the oral hygiene status of special needs children. Keywords: parental care; oral hygiene; special needs children Abstrak: Masalah kebersihan gigi dan mulut pada anak berkebutuhan khusus (ABK) merupakan prioritas yang perlu mendapat perhatian semua pihak yaitu orang tua, pengasuh, dokter gigi dan pengampu kebijakan kesehatan baik nasional maupun daerah sedini mungkin. Penelitian ini bertu-juan untuk mengetahui hubungan antara tingkat kepedulian orang tua dengan oral hygiene anak SLB Wacana Asih, Kota Padang. Jenis penelitian ialah survei analitik dengan desain potong lintang. Metode pengambilan sampel ialah total sampling yaitu orang tua dari ABK dan ABK sebanyak 82 anak. Data penelitian diuji menggunakan uji Spearman Rank dengan tingkat signifikansi p<0,05. Hasil penelitian menunjukkan bahwa kepedulian orang tua tentang kebersihan gigi dan mulut ABK dengan kategori baik sebanyak 53,66%, sedangkan kategori cukup baik sebesar 46,445%. Hasil pemeriksaan status oral hygiene ABK menunjukkan berbagai level status yakni: baik (45,1%), sedang (28%) dan buruk (26,8%). Hasil uji korelasi mendapatkan p=0,000 yang menunjukkan hubungan bermakna anatara kepedulian orang tua dengan status oral hygiene ABK dengan nilai koefisien korelasi r 0.699 yang bermakna hubungan positif kuat. Simpulan penelitian ini ialah sema-kin tinggi kepedulian orang tua maka akan semakin baik status oral hygiene berkebutuhan khusus. Kata kunci: kepedulian orang tua; oral hygiene; anak berkebutuhan khusus